Supplemental Fig. S3 - Dominik Leitz (16907277) (2024)
Survival of conditional Nedd4-2-/- and control mice in the two study groups. (a) Kaplan-Meier curves from conditional Nedd4-2-/- and control mice of the cross-sectional (a) and longitudinal study group (b). n = 5-12 mice/group.